2017
DOI: 10.1128/jb.00890-16
|View full text |Cite
|
Sign up to set email alerts
|

Active Multienzyme Assemblies for Long-Chain Olefinic Hydrocarbon Biosynthesis

Abstract: Bacteria from different phyla produce long-chain olefinic hydrocarbons derived from an OleA-catalyzed Claisen condensation of two fatty acyl coenzyme A (acyl-CoA) substrates, followed by reduction and oxygen elimination reactions catalyzed by the proteins OleB, OleC, and OleD. In this report, OleA, OleB, OleC, and OleD were individually purified as soluble proteins, and all were found to be essential for reconstituting hydrocarbon biosynthesis. Recombinant coexpression of tagged OleABCD proteins from Xanthomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It is hypothesized that the final decarboxylation to form the cis -olefin product is catalyzed by OleB (α/β-hydrolase superfamily) [10]. OleBCD were proposed to form a multi-enzyme assembly that may function to efficiently move the hydrophobic pathway intermediates between enzyme active sites, preserve the stereochemistry, and sequester the highly reactive β-lactone from the cell [11]. As well as initiating the pathway, OleA has been proposed to act as a shuttle between fatty acid metabolism and the OleBCD assembly feeding its β-keto acid product to OleD [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the final decarboxylation to form the cis -olefin product is catalyzed by OleB (α/β-hydrolase superfamily) [10]. OleBCD were proposed to form a multi-enzyme assembly that may function to efficiently move the hydrophobic pathway intermediates between enzyme active sites, preserve the stereochemistry, and sequester the highly reactive β-lactone from the cell [11]. As well as initiating the pathway, OleA has been proposed to act as a shuttle between fatty acid metabolism and the OleBCD assembly feeding its β-keto acid product to OleD [11].…”
Section: Introductionmentioning
confidence: 99%
“…The lactone synthase OleC forms a heat-labile internal ester between the β-hydroxy and the carboxyl group and one molecule of water is released. Finally, the lactone decarboxylase OleB liberates one molecule of CO 2 and converts the internal lactone into an alkene with a cis-configured internal double bond (internal olefins) at the connection point of the two original fatty acid precursors (Beller et al [3]) (Sukovich et al [14]) (Frias et al [7]) (Christenson et al [4]) (Christenson, Richman et al [6]) (Christenson, Jensen et al [5]).…”
Section: Open Accessmentioning
confidence: 99%
“…The nature of such internal olefin hydrocarbons was first characterized in the Gram-positive Sarcina lutea (now Kocuria rhizophila) (Albro and Dittmer [1]) (Tornabene et al [17]), and the oleABCD genes were first described in the Gram-positive Micrococcus luteus NCTC2665 (Beller et al [3]). Nevertheless, the catalytic mechanism of OleA as well as the order and nature of the reaction steps of the OleABCD enzymes, as summarized above, were finally elucidated mainly in the Gram-negative species Shewanella oneidensis (Sukovich et al [14]) and Xanthomonas campestris (Frias et al [7]) (Christenson et al [4]) (Christenson et al [6]) (Christenson et al [5]). In addition, the first report on the phylogenetic distribution and diversity of olefin production in bacteria by Sukovich et al [13] described bacterial olefin production as a predominately Gram-negative capability using species from four Gram-negative phyla (Proteobacteria, Planctomycetes, Chloroflexi, Verrucomicrobia) and one Gram-positive phylum (Actinobacteria) (Sukovich et al [13]).…”
Section: Open Accessmentioning
confidence: 99%
“…OleC, a β-lactone synthetase, then generates a β-lactone moiety (Christenson et al, 2017b) which is subsequently de-carboxylated by OleB, a β-lactone decarboxylase, yielding the final olefin product (Christenson et al, 2017c). Recent work has demonstrated that OleBCD together form a large multimeric enzyme complex that processes the β-keto intermediate formed by OleA activity (Christenson et al, 2017a). Weak interactions between the OleBCD complex and OleA in vitro suggests that OleA condenses the precursor acyl groups and possibly transfers the β-keto acid product directly to the OleBCD complex for further processing (Christenson et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that OleBCD together form a large multimeric enzyme complex that processes the β-keto intermediate formed by OleA activity (Christenson et al, 2017a). Weak interactions between the OleBCD complex and OleA in vitro suggests that OleA condenses the precursor acyl groups and possibly transfers the β-keto acid product directly to the OleBCD complex for further processing (Christenson et al, 2017a). In the absence of downstream processing by OleBCD, the OleA catalyzed β-keto acid intermediate undergoes spontaneous decarboxylation to form a ketone product (Sukovich et al, 2010b; Frias et al, 2011; Figure 1).…”
Section: Introductionmentioning
confidence: 99%